A reflection on the challenges in Nigerian agricultural policies and the way forward / Abdul Rauf Ambali and Asimiyu Olalekan Murana - Ambali, Abdul Rauf; Murana, Asimiyu Olalekan (Universiti Teknologi MARA, Shah Alam, 2017)
This study examines the Nigerian Agricultural Policies before and after independence. The paper employs secondary source of collecting data. The study reveals that despite the soundness of most of the Nigerian Agricultural Policies, there is a real short fall between the expectations and results. It also identified some of the challenges of the reviewed policies which have been hitherto affecting the translation of these ambitious policy documents into realities. Based on the findings of this paper, it was recommended that government should redouble its efforts in implementing various policies and programmes, adopting a consistent policy measures, avoiding unjustifiable policy reversals, partnering with relevant inter-governmental organizations in order to attract the much-needed private sector capital injections into the agricultural sector, as well as increasing the expertise to make the sector become the engine of growth in Nigeria.